Communication and media policies in convergence environments in Latin America: cases from Uruguay and Colombia - Beltramelli, Federico (2018)
This paper contributes for the research agenda located at the intersection of processed normative changes and the advancement of new convergent technologies for the Audiovisual Communication Services (ACS) sector. It is based on a systematization of two cases (Colombia and Uruguay) which trends of communication policies are identified, evidencing similarities and differences of each country, institutional architectures and recent regulatory changes in order to review the challenges and perspectives for formulate communication and media policies within the framework of technological transformations